2016
DOI: 10.1007/s00056-016-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel ion concentrations in the saliva of patients treated with self-ligating fixed appliances: a prospective cohort study

Abstract: OBJECTIVE Orthodontic appliances are considered to be highly biocompatible although adverse effects attributed to the release of nickel ions (Ni(2+)) have been documented. Self-ligating brackets have grown in popularity for economic reasons and supposed friction reduction. The aim of the present prospective cohort study was therefore to determine salivary Ni(2+) concentrations in patients undergoing orthodontic treatment with self-ligating fixed appliances. MATERIALS AND METHODS A group of 30 patients between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 47 publications
1
28
1
2
Order By: Relevance
“…Such alloys are mainly composed of 68-80% nickel and 12-26% chromium but they also contain other elements in quantities varying from 0.1 to 14% [1,2]. Recent studies indicate an increased release of nickel from orthodontic appliances into the artificial saliva or into human salivary secretions [3][4][5]. Moreover, a few studies have demonstrated a positive correlation between the enhanced nickel concentration in oral mucosa cells released from fixed orthodontic appliances and DNA damage as well as increased number of apoptotic cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Such alloys are mainly composed of 68-80% nickel and 12-26% chromium but they also contain other elements in quantities varying from 0.1 to 14% [1,2]. Recent studies indicate an increased release of nickel from orthodontic appliances into the artificial saliva or into human salivary secretions [3][4][5]. Moreover, a few studies have demonstrated a positive correlation between the enhanced nickel concentration in oral mucosa cells released from fixed orthodontic appliances and DNA damage as well as increased number of apoptotic cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel-containing alloys exist in a wide variety of appliances and auxiliary devices used in orthodontics, with a content of up to 55% by weight. Likewise, the in vivo release of nickel ions varies greatly, from 0.5 to 105.7 μg/l, according to the alloy type, body fluid, temperature, mechanical stress, or pH (8,9). In general, orthodontic materials are considered to be highly biocompatible (10).…”
mentioning
confidence: 99%
“…Stainless steel brackets are the most widely used due to their good mechanical properties, corrosion resistance and biocompatibility [1]. Despite their high corrosion resistance, stainless-steel brackets can corrode in the oral environment [4].…”
Section: Discussionmentioning
confidence: 99%
“…Stainless-steel brackets remain in patients' mouths for extended periods, during which the brackets are exposed to chemical and physical processes that can damage the metal structure, resulting in decreased corrosion resistance [1,2]. A study indicated that in addition to environmental conditions in the oral cavity, thermal recycling (direct flaming) can affect the stability of the metal ion content of the bracket, resulting in the release of metal ions and the decrease of corrosion resistance of the bracket [3].…”
Section: Introductionmentioning
confidence: 99%